ENHANCING BUSINESS PROCESS ORGANIZATION: A COMPREHENSIVE ANALYSIS OF KEY FACTORS AND MODELS - Nutfulloev Tolib G’olib o’g’li (Journals Park Publishing, 2023)
This article provides an in-depth analysis of factors, strategies, and fundamental principles influencing the organization of business processes in contemporary business entities. Through the lens of various models and theories, this research aims to offer valuable insights into optimizing organizational efficiency and adaptability.
Keywords: Business Process Automation, Business Process Model, managing employees, organization, quality management, cоnsumer behаviоr, cоmpetitiveness, cоmpetitiоn, key figures, evаluаtiоn, оrgаnizаtiоn, digital transformation.